Effects of serial radon spa therapy on pain and peripheral immune status in patients suffering from musculoskeletal disorders– results from a prospective, randomized, placebo-controlled trial - Donaubauer, Anna-Jasmina; Becker, Ina; Klein, Gerhart; Voll, Reinhard E.; Weikl, Lena; Klieser, Martin; Barzangi, Shakar; Zhou, Jian-Guo; Fietkau, Rainer; Gaipl, Udo S.; Frey, Benjamin (Frontiers in Immunology, 2024)
In this randomized, placebo-controlled cross-over trial we aimed to investigate if radon spa therapy exerts more pain relief than exposure to warm water alone. In addition, immunological parameters were assessed in both treatment groups. In the RAD-ON02 trial, 116 patients suffering from musculoskeletal disorders (MSDs) received either serial radon spa or solely warm water baths. Pain intensity was assessed by determination of different pain parameters on a visual analogue scale and by pressure point dolorimetry at baseline and at weeks 4, 12 and 24. The longitudinal immune status of the patients was analyzed by a flow cytometry-based assay from peripheral blood at the time points of pain assessments. There were no side effects attributable to radon exposure observed. However, radon spa was superior to warm water applications at week 4 in terms of pain reduction. Pain and morning stiffness at the time of assessment were significantly reduced after radon spa (p<0.001, p<0.01) but not after warm water baths. The dolorimetry resulted in a significantly higher exerted pressure strength in patients after radon spa (p<0.001), but not after warm water applications. During the long-term follow-up, both treatment modalities reduced pain to a similar degree and pain modulation was not distorted by the participants' intake of analgesics. No significant changes in the immune status attributable specifically to radon were found, even though the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water baths and a higher level of significance is reached after radon spa at week 24. Serial radon spa has additive pain-relieving effects. The immunological parameters assessed in our study appear not to be directly linked to the pain reduction caused by radon exposure, at least in MSD patients with predominantly degenerative diseases.Trial registration: The RAD-ON02 trial is registered on the European Union Drug Regulating Authorities Clinical Trials Database (EudraCT): 2016-002085-31 and on the Deutsches Register Klinischer Studien (DRKS): DRKS00016019.